2006
DOI: 10.1021/jp055934u
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Paraffin Deposition under High Flow Rate as a Function of the Crude Oil Paraffin Type and Content by Fluorescence Depolarization:  Polypropylene and High-Density Polyethylene

Abstract: High-density polyethylene (HDPE) and polypropylene (PP) were studied to identify tailor-made materials for walls of pipelines and ducts for crude paraffinic oil that inhibit paraffin depositions. The interfacial interaction was investigated from 50 to 70 degrees C and as a function of the n-C(36)H(74) paraffin concentration added to the paraffinic crude oil. The static and the dynamic interfacial tensions were observed, respectively, by traditional contact angle measurements and by fluorescence depolarization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…11 For instances, high-density polyethylene and polypropylene were studied to identify tailor-made materials for walls of pipelines and ducts for crude paraffinic oil that inhibit paraffin depositions. 12,13 Copolymers of alkyl acrylates [14][15][16] have been found to act either as wax growth inhibitors or promoters with different degrees of polymerization. Poly(ethylene-butene) random copolymers were reported to co-crystallize with waxes into thin platelets so as to modify the wax crystal morphology through microscopy and calorimetric studies 17,18 and small-angle neutron scattering (SANS) techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 For instances, high-density polyethylene and polypropylene were studied to identify tailor-made materials for walls of pipelines and ducts for crude paraffinic oil that inhibit paraffin depositions. 12,13 Copolymers of alkyl acrylates [14][15][16] have been found to act either as wax growth inhibitors or promoters with different degrees of polymerization. Poly(ethylene-butene) random copolymers were reported to co-crystallize with waxes into thin platelets so as to modify the wax crystal morphology through microscopy and calorimetric studies 17,18 and small-angle neutron scattering (SANS) techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the wide variety of oil components, many kinds of polymers were developed as PPD additives to affect the flow property of oil via adjusting the precipitation of wax crystals , C opolymers of alkyl acrylates have been found to act either as wax growth inhibitors or promoters with different degrees of polymerization. Poly(ethylene−butene) random copolymers were reported to co-crystallize with waxes into thin platelets so as to modify the wax crystal morphology through microscopy and calorimetric studies , and small-angle neutron scattering (SANS) techniques .…”
Section: Introductionmentioning
confidence: 99%
“…In the past, several research groups dedicated time and effort to investigate the physicochemical mechanisms that lead to the formation of paraffinic deposits, as well as to develop methods to prevent the formation of these crystals and the consequent stagnation of oil production and transport [2][3][4][5]. Several techniques have been used to determine the properties such as thermal diffusivity, heat capacity, (paraffin) molecular diffusion coefficient, and kinematic viscosity, with the aim of developing alternative methods to characterize the types of oil [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…They may be used either as coatings or linings for metallic ducts or as massive ducts. Although they cannot stand high temperatures and their low mechanical resistance is a concern, they have the advantage of impeding the formation of paraffin deposits and a much lower corrosion rate than unlined metallic ducts. They are already being used to recuperate condemned metallic ducts by insertion of a plastic layer as inner lining, thus reducing the costs of welding and equipment maintenance or replacement.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was observed that θc could not discriminate between the interactions with polyethylene surfaces with different branching degrees. 16 It was also shown 3,4,[17][18][19][20] that θc characterization cannot be applied straightforwardly to interactions between walls and liquids flowing at high rates as it becomes unreliable due to not taking into account flow effects within the liquid like molecular chains orientation.…”
Section: Introductionmentioning
confidence: 99%